Can Ministers Lead Sports Federations? Examining Power and Dual Roles in Indonesia’s Constitution - Fadhlilah, Muhammad Rizqi; Anggraeni, Aprili Naufal; Yusuf, Yusmedi; Pangestu, Ilham Aji (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
The practice of dual ministerial roles, including leadership in sports federations, is a growing phenomenon in Indonesia, despite being explicitly prohibited by Article 23 of Law Number 39 of 2008. This study investigates the legal and constitutional implications of such dual roles, particularly focusing on ministers concurrently serving as heads of sports federations. Employing a normative research method, the findings reveal a conflict between the legal framework and current practices. Although the law forbids ministers from holding dual positions in organizations funded by state budgets, such roles remain valid under state recognition, creating a significant legal paradox. This paper argues that the President must enforce dismissal for ministers violating Article 23 to uphold the rule of law and prevent potential abuse of power. The study underscores the urgency of addressing this issue to safeguard public trust and ensure compliance with Indonesia’s constitutional principles.